Meningkatkan Hasil Belajar Matematika Melalui Media Bangun Ruang pada Siswa Kelas V Di SDN. No. 025/XI Desa Gedang - Neneng Triyuna (Universitas Batanghari Jambi, 2018)
This study aims to improve student learning outcomes in mathematics subjects by using space wake media in fifth grade students at SDN. No. 025/XI Gedang Village. This research is a classroom action research conducted in two cycles. Each cycle consists of four activities, namely planning, implementation, observation, and reflection. The study involved 20 fifth grade students year 2017/2018 at SDN. No. 025/XI Gedang Village, Sungai Penuh District, Sungai Penuh City, Jambi Province. This research was conducted for three months from September to November of 2017. Data collected in this study is students learning outcomes. Data were collected by observation and test. Furthermore, the data were analyzed by using descriptive analysis and simple statistical test. The results showed that student activity in learning improved. The increasing of student activity can be seen from from the increasing spirit of students in following the series of learning activities. Students are more active during lesson activities, students are able to ask questions, and students are able to answer the test questions well. Increasing of student learning activities are also in tandem with improving student learning outcomes. The average score of student learning outcomes increased from 61.50 before the action was given to 76.0 in cycle I and increased again to 80.25 in cycle II. Likewise with learning mastery. Learning completeness increased from 25.00% before the action was given to 80.00% in cycle I and increased again to 100.00% in cycle II. Thus, the use of build space media in the mathematics subjects can improve activity and learning outcomes of fifth grade students at SDN. No. 025/XI Gedang Village year 2017/2018.